Prevalence and Associated Risk Factors of Hepatitis B Virus Infection Among Healthcare Professionals in a Tertiary Care Hospital in Nigeria: ACross Sectional Study (Western Journal of Medical and Biomedical Sciences, 2023)
This study investigated the prevalence and risk factors of hepatitis B virus (HBV) infection among healthcare professionals (HCPs) in a tertiary care hospital in Nigeria. Of the 355 participants, 7.3% were infected with HBV, with nurses having a highest prevalence rate of7.2%. Multivariate analysis identified age group 30-39 and a history of needle-stick injury as independent risk factors for HBV infection. Only 40.3% of HCPs had received complete HBVvaccination, with 31.0% reporting incomplete vaccination and 28.2% having had no vaccination. The study highlights the importance of implementing comprehensive HBVvaccination programs and strict adherence to infection control guidelines to prevent occupational transmission of HBVamong HCPs in Nigeria. The findings also emphasize the need for increased awareness of the risk factors associated with HBV infection among HCPs. These insight scan guide the development of effective public health policies aimed at reducing the burden of HBV infection in the healthcare sector.
Keywords: Hepatitis B virus; Hospital care professionals; Prevalence; Needle-stick